Comparative Study: Passenger Satisfaction on ASDP Ferry and Dharma Lautan Ferry to Selayar - Sulastriani R; Diah Vitaloka; Ika Mustika (International Journal of Health Engineering and Technology, 2026)
This study aims to identify the level of passenger satisfaction with the services provided by the ASDP ferry and the Dharma Lautan ferry on the Selayar route, the factors that influence passenger satisfaction on both ferries and a comparison between the quality of service and the operation of the two vessels. Passenger satisfaction is measured based on indicators: service quality (staff friendliness, responsiveness), ship facilities (seat comfort, cleanliness, and additional facilities), and punctuality of departure and arrival. Service quality is assessed based on passenger perceptions of indicators such as service speed, staff friendliness, and punctuality. Ship operation is assessed from the aspects of facility comfort, departure frequency, and operational efficiency. This study uses a descriptive quantitative approach with a comparative method to compare the level of passenger satisfaction between two ship operators, namely PT ASDP Indonesia Ferry and Dharma Lautan Nusantara. Based on the results of the study, the average value (mean score) of the two vessels has a difference of approximately 8 points. The average level of customer satisfaction of the ASDP ferry is 64.68 while the average level of customer satisfaction of the Dharma Lautan is higher at 72.96. This figure shows that statistically, Dharma Lautan ship customers are generally more satisfied than ASDP ship customers. Factors that influence passenger satisfaction: On-time departure schedule; Crew service; Ship cleanliness and facilities; Ticket price; Passenger boarding and disembarkation process. Research shows that the percentage comparison of passenger satisfaction on these two ships is significantly different where the Dharma Lautan Utama ship has a high percentage on each satisfaction assessment indicator, while the ASDP ferry ship is only in the highest percentage range of 30%.